Prevention of Occupational Heat-Related Illnesses. Issue 10 (October 2021) - Tustin, Aaron; Sayeed, Yusef; Berenji, Manijeh; Fagan, Kathleen; McCarthy, Ronda B.; Green-McKenzie, Judith; McNicholas, James; Onigbogi, Charles Babajide; Perkison, William Brett; Butler, James W.
Abstract : : High ambient temperatures and strenuous physical activity put workers at risk for a variety of heat-related illnesses and injuries. Through primary prevention, secondary prevention, and treatment, OEM health providers can protect workers from the adverse effects of heat. This statement by the American College of Occupational and Environmental Medicine provides guidance for OEM providers who serve workers and employers in industries where heat exposure occurs.